Determinación del nivel de eutrofización del agua de la Laguna de Atocha de la parroquia Cusubamba ubicada en el cantón Salcedo, provincia de Cotopaxi período 2017-2018. - Toapaxi Quispe, Gabriela Estefania (2018)
The Atocha Lake is located in Cusubamba Town Cotopaxi Province Salcedo Canton to an altitude of 3576 meters above sea level, the main goal of the yob was to determine the eutrophication level of water from the lake, samplings were carried out, one during dry season (April ) and the other one on rainy season (June), in order to make a more objective evaluation, parameters of conductivity, dissolved oxygen (DO), hydrogen potential (pH), turbidity, nitrates and temperature were measured, verifying that they are within the maximum permissible limits of the current national environmental regulations, besides the concentration value of chlorophyll "a" was analyzed with (7.82 mg / m3) during dry season, and (7.05 mg / m3) on rainy time respectively, total phosphorus with (16.67mg / m3) on stillage time, and (14.45 mg / m3) on rainy season, data that allowed to establish the degree of water’s eutrophication, using the Index of the Trophic State. The results show that Atocha Lake is in a mesotrophic state, where the main causes that affect this resource are the livestock activity, disposal of solid waste into the lake. It is important to take into account the sectorization of grazing areas with the objective to controlli livestock pressure and the creation of protected areas that make possible the recovery of natural pastures in the area. In addition, it is necessary to train local people to promote good environmental practices, but the most important the commitment of the competent authorities to create and apply policies on the protection, conservation, and control of water resources, through the application of ordinances by the authority to engage the participation of society in general.